Juridical Analysis Of The Role Of Investigators In The Perspective Of Combating Criminal Acts Of Fraud Through Check Securities : Research Study At The Barelang Police Criminal Investigation Unit - Ade Putra; Erniyanti Erniyanti; M. Soerya Respationo (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
Fraud through cheque securities is a form of economic crime that harms many parties, both individuals and financial institutions. The background of this problem is the increasing number of fraud cases involving blank checks in Batam City, which causes significant financial losses and reduces public confidence in these payment instruments. This study aims to analyze the role of investigators in eradicating fraud through cheque securities, with a focus on the Barelang Police Criminal Investigation unit. This study uses a normative juridical method with a case study approach, involving analysis of primary and secondary data in the form of interviews with investigators, literature reviews, and document studies related to check fraud cases in the jurisdiction of the Barelang Police. The results of the study show that investigators have a crucial role in handling fraud cases through cheque securities, starting from receiving reports and complaints, collecting and securing evidence, to preparing case files for prosecution. However, there are several obstacles that reduce the effectiveness of investigations, such as lack of resources, lack of specialization in financial crimes, and limited access to information. To overcome these obstacles, this study provides several recommendations, including increasing the capacity and expertise of investigators through ongoing training, increasing budgets and technological resources, and strengthening cooperation between investigators and other financial institutions and law enforcement. The suggestions put forward in this study are that police investigators should improve internal and external coordination to speed up the investigation process, other law enforcers such as prosecutors and judges should increase collaboration with investigators to ensure a fair and transparent judicial process, and the public, especially victims of cheque fraud, should be educated on the steps to be taken when becoming victims of fraud. With the implementation of this recommendation, it is hoped that the handling of fraud cases through check securities can be more effective and public trust in the justice system can increase.